(untitled) (Bangladesh Journal of Agricultural Research, 2023)
An investigation was carried out on snake gourd at the research farm of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Bangladesh during March to June 2019. Significant heterosis was observed for most of the characters studied to find out high heterotic combination for better hybrids. Both positive and negative heterosis were found for different characters of the F1 hybrids over better parents. The best better parent heterotic performance was exhibited by early flowering and fruit fly infestation in P2 x P7 and P6 x P7, respectively while P3 x P7 for higher individual fruit weight; P1 x P3, P2 x P6, P3 x P7, P4 x P6 for number of fruit bearing; P1 x P3, P2 x P3, P2 x P7, P3 x P7, for higher fruit yield per plant and hectare; P1 x P3, P2 x P3, P2 x P6, P3 x P7 for maximum fruit length P2 x P6, P4 x P6, P4 x P7 for fruit diameter as well as for increasing 100-seed weight the cross combinations were P2 x P3, P4 x P6. Based on all the characters and heterotic performance, the crosses combinations viz., P1 x P3, P2 x P6, P3 x P7 and P6 x P7 can be selected to exploit improved hybrid lines. Bangladesh J. Agril. Res. 47(1): 1-12, March 2022